Happy to Be a Boss? Cultural Moderators of Relationships Between Supervisory Responsibility and Job Satisfaction - Jaakson, Krista; Ashyrov, Gaygysyz (Frontiers in Psychology, 2022)
This paper addresses whether supervisory responsibility is a challenging job demand in the Job Demands-Resources (JD-R) model in different cultural contexts. We investigate how job satisfaction responds to a supervisory role with job control and selected cultural dimensions using a cross-cultural dataset of 14 countries with more than 43,000 adults using ordered logit regression models. We find that a supervisory role enhances job satisfaction and appears to be a challenging job demand. However, no studied cultural dimension, masculinity, power distance, individualism, or uncertainty avoidance, increases job satisfaction derived from this kind of responsibility. Our study indicates that there might be stereotypical assumptions about cultural dimensions concerning the job satisfaction of supervisors.